Effect of the synthesis method and praseodymium on the electrical properties of Mg-Cubic Zirconia - Badenes, J. (Boletín de la Sociedad Española de Cerámica y Vidrio, 1999)
The synthesis of nanostructured Mg-FSZ fully stabized zirconia by chemical methods such as colloidal gel, polyester resin and hydrolisis of alkoxides has been studied. The addition of praseodymium ion facilitates cubic stabilization avoiding the Mg- FSZ partitioning with temperature. Praseodymium improve the ionic conductivity of the material probably by the entrance of Pr3+ on the host lattice substitting Zr4+ and subsequently introduction of additional oxygen vacancies trapped near the zirconium ion. En este trabajo se estudia la obtención de circona cúbica estabilizada con magnesio nanoestructurada por métodos químicos tales como el gel coloidal, resina poliester de citrato así como hidrólisis de alcóxidos. La adición de praseodimio mejora la reactividad del sistema y evita la transformación a monoclínica con la temperatura. Asimismo el praseodimio mejora la conductividad iónica del material por un mecanismo de disolución sólida de modo que el Pr3+ introduce nuevas vacantes de oxígeno que podrían quedar asociadas a iones circonio en la red.